A Standardized Patient Counseling Rubric for a Pharmaceutical Care and Communications Course - Horton, Niambi (American Journal of Pharmaceutical Education, 2013)
Objective. To restructure a required pharmaceutical care and communications course to place greater emphasis on communication skills and include a high-stakes assessment. Design. A standardized counseling rubric was developed for use throughout the pharmacy curriculum and the counseling laboratory practicals were changed to high-stakes assessments. Assessment. An annual mid-semester and end-of-semester high-stakes patient-counseling objective structured clinical examination (OSCE) conducted prior to and after revision of the course and counseling rubric documented improvements in students’ scores. Performance on the post-course annual assessment patient counseling OSCE improved compared to that on the pre-course (p<0.001). Conclusion. The 2010 course revision improved students’ medication counseling abilities and readiness to practice. Major course revisions should be undertaken only after input from all stakeholders and with data to support the need for change.